Functional and Well‐Defined β‐Sheet‐Assembled Porous Spherical Shells by Surface‐Guided Peptide Formation. (3rd April 2015) - Wibowo, Steven Harris; Sulistio, Adrian; Wong, Edgar H. H.; Blencowe, Anton; Qiao, Greg G.
Abstract : Polypeptides have attracted widespread attention as building blocks for complex materials due to their ability to form higher‐ordered structures such as β ‐sheets. However, the ability to precisely control the formation of well‐defined β ‐sheet‐assembled materials remains challenging as β ‐sheet formation tends to lead to ill‐defined and unprocessable aggregates. This work reports a simple, rapid, and robust strategy to form well‐defined peptide β ‐sheet‐assembled shells (i.e., hollow spheres) by employing surface‐initiated N ‐carboxyanhydride ring‐opening polymerization under a highly efficient surface‐driven approach. The concept is demonstrated by the preparation of enzyme‐degradable rigid shell architectures composed of H‐bonded poly(L‐valine) (PVal) grafts with porous and sponge‐like surface morphology. The porous PVal‐shells exhibit a remarkable and unprecedented ability to non‐covalently entrap metal nanoparticles, proteins, drug molecules, and biorelevant polymers, which could potentially lead to a diverse range of biodegradable and functional platforms for applications ranging from therapeutic delivery to organic catalysis. Abstract : Well‐defined peptide β ‐sheet‐assembled porous shells with tailored dimensions are prepared by a simple, rapid, and robust bottom‐up strategy involving surface‐initiated ring‐opening polymerization. Further exploitation of the hollow shells demonstrates the ability to non‐covalently entrap small molecules, nanoparticles, proteins, drugs, and polymers to form functional materials for various potential applications.